The Role of Adolescence in Development Paths Toward Suicide: Specificities and Shaping of Adversity Trajectories - Notredame, Charles-Edouard; Chawky, Nadia; Beauchamp, Guy; Vaiva, Guillaume; Séguin, Monique (Frontiers in Psychiatry, 2020)
Purpose. Adolescence is a key period of transitions in the psychological, cognitive, neurobiological and relational domains, which is associated to high susceptibility to adverse life experiences. However, the way adolescent development alters life paths towards suicide remains unclear. Thereby, we aimed at testing whether and how adolescence interfered with the adversity trajectories of individuals who died by suicide. Methods. In a sample of 303 individuals who died by suicide, longitudinal Burden of Adversity ratings were derived from extensive psychological autopsies and life trajectory narrative interviews conducted with informants. Piecewise Joint Latent Class Models allowed the identification of patterns of adversity trajectories and tested the introduction of breakpoints in life-paths. Classes inferred from the optimal model were compared in terms of socio-demographics, psychopathology, and rate of different adverse life events. Results. The most accurate model derived 2 trajectory patterns with a breakpoint in early adolescence. In the first class (n = 39), the burden of adversity increased steadily from birth to death, which occurred at 23 (SE = 1.29). In the second class (n = 264), where individuals died at 43 years of age (SE = 0.96), the burden of adversity followed a similar trajectory during infancy but stabilized between 10 and 14 years and started to increase again at about 25. Childhood family instability, dependent events, exposure to suicide, intra-family sexual victimization and affective disorders at death were more frequent in class 1. Conclusions. A bifurcation in trajectories between early and late suicides occurs during adolescence. The dynamic pattern of adversity during this period is a key issue to understand the developmental heterogeneity in suicide risk.